Positive electrode sheet and preparation method and application thereof
By using the three-layer active layer structure of Prussian blue compound, layered oxide and polyanionic compound in the positive electrode sheet of the sodium ion battery, the problems of low energy density and poor cycle stability of sodium ion battery are solved, and the battery performance with high specific capacity, energy density and cycle stability are achieved.
Patent Information
- Application Number
- CN202410832259.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-04-04
AI Technical Summary
The low energy density and poor cycle stability of existing sodium ion batteries limit their application in the high-end automobile field.
The positive electrode sheet of three active layers is used, and the active layer is laminated with Prussian blue compound, layered oxide and polyanionic compound, and the specific capacity, energy density and cyclic stability are improved through synergistic action.
It significantly improves the specific capacity of the positive electrode plate and the energy density of the battery, enhances the cycle stability, and makes the battery suitable for high-end automotive applications.
Smart Images

Figure CN119764343A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to positive electrode plates and preparation methods and applications thereof. Background Art
[0002] Sodium-ion batteries have become a current research hotspot because of their high raw material reserves, low price, high safety, and wide operating temperature range. However, the low energy density and poor cycle stability of sodium-ion batteries limit their application in the field of high-end automobiles. In related technologies, the energy density and cycle stability of batteries can be improved by modifying the positive electrode materials. However, at present, the modification of positive electrode materials has limited effect on the improvement of battery energy density and cycle performance, and industrial preparation is difficult to implement. Therefore, there is a need for a positive electrode sheet that is conducive to industrialization, has good cycle stability, high specific capacity, and excellent energy density. Summary of the invention
[0003] In view of this, the present application provides a positive electrode plate and a preparation method and application thereof. The active layer of the positive electrode plate has three types of stacked positive electrode active materials: Prussian blue compound, layered oxide and polyanion compound. Under their synergistic effect, the specific capacity of the positive electrode active layer, the energy density and cycle stability of the battery are improved.
[0004] In a first aspect, the present application provides a positive electrode plate, comprising a positive electrode collector and an active layer arranged on at least one side of the positive electrode collector, wherein the active layer comprises a first active layer, a second active layer and a third active layer stacked in sequence from a side close to the positive electrode collector to a side away from the positive electrode collector, the first active layer comprises a first active material, the second active layer comprises a second active material, the third active layer comprises a third active material, the first active material, the second active material and the third active material are selected from three types of active materials: Prussian blue compounds, layered oxides or polyanion compounds, and the first active material, the second active material and the third active material are different types of active materials.
[0005] Optionally, the second active material is a layered oxide.
[0006] Optionally, the first active material is a Prussian blue compound, the second active material is a layered oxide, and the third active material is a polyanion compound.
[0007] Optionally, in the active layer, the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is (1.5-2.5):(4-6):(2.5-3.5).
[0008] Optionally, in the first active layer, the mass percentage of the first active material is 90%-97%; in the second active layer, the mass percentage of the second active material is 90%-97%; in the third active layer, the mass percentage of the third active material is 90%-97%.
[0009] Optionally, the Prussian blue compound includes Na2Zn3[Fe(CN)6]2·xH2O (x≤0.1), Na 1.72 MnFe(CN)6、Na 1.92 At least one of FeFe(CN)6 and Na2CoFe(CN)6.
[0010] Optionally, the layered oxide includes at least one of sodium nickelate, sodium ferrite, sodium chromate, copper iron manganese oxide and sodium ferrite-based oxide.
[0011] Optionally, the polyanion compound includes at least one of sodium iron sulfate, sodium iron phosphate, sodium vanadium phosphate and sodium vanadium fluorophosphate.
[0012] Optionally, the first active layer further includes a conductive agent and a binder; the second active layer further includes a conductive agent and a binder; and the third active layer further includes a conductive agent and a binder.
[0013] Optionally, the third active material is a polyanion compound, the mass content of the conductive agent in the third active layer is greater than the mass content of the conductive agent in the first active layer; and / or the mass content of the conductive agent in the third active layer is greater than the mass content of the conductive agent in the second active layer.
[0014] Optionally, in the first active layer, the mass ratio of the first active material, the conductive agent and the binder is (94.5-96.5):(1.5-3):(2-2.5); in the second active layer, the mass ratio of the second active material, the conductive agent and the binder is (94.5-96.5):(1.5-3):(2-2.5); in the third active layer, the mass ratio of the third active material, the conductive agent and the binder is (94.5-96.5):(1.5-3):(2-2.5).
[0015] The positive electrode plate provided in the present application includes three active layers, which include different types of active materials. The positive electrode plate combines the advantages of Prussian blue compounds, layered oxides and polyanion compounds, and through the synergistic effect of the combination of the three materials, the specific capacity, cycle stability and energy density of the positive electrode plate are improved.
[0016] In a second aspect, the present application provides a method for preparing a positive electrode sheet, comprising:
[0017] The first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry are sequentially coated on at least one side of the surface of the positive electrode collector, and a positive electrode sheet is obtained after drying; the first positive electrode slurry includes a first active material, the second positive electrode slurry includes a second active material, the third positive electrode slurry includes a third active material, the third active layer includes a third active material, the first active material, the second active material and the third active material are selected from three types of active materials: Prussian blue compounds, layered oxides or polyanion compounds, and the first active material, the second active material and the third active material are different types of active materials.
[0018] Optionally, the first positive electrode slurry further includes a conductive agent and a binder, and the mass ratio of the first active material, the conductive agent and the binder in the first positive electrode slurry is (94.5-96.5):(1.5-3):(2-2.5).
[0019] Optionally, the second positive electrode slurry further includes a conductive agent and a binder, and the mass ratio of the second active material, the conductive agent and the binder in the second positive electrode slurry is (94.5-96.5):(1.5-3):(2-2.5).
[0020] Optionally, the third positive electrode slurry further includes a conductive agent and a binder, and the mass ratio of the third active material, the conductive agent and the binder in the third positive electrode slurry is (94.5-96.5):(1.5-3):(2-2.5).
[0021] Optionally, the viscosity of the first positive electrode slurry is 1500 Pa·s-8000 Pa·s;
[0022] The viscosity of the second positive electrode slurry is 1500Pa·s-8000Pa·s;
[0023] The viscosity of the third positive electrode slurry is 1500 Pa·s-8000 Pa·s.
[0024] The preparation method of the positive electrode plate provided in the present application is novel, the preparation process is simple, the prepared positive electrode plate has high energy density, good specific capacity, and excellent cycle performance, and can be applied industrially.
[0025] In a third aspect, the present application provides a battery, comprising a positive electrode sheet and a negative electrode sheet, and a separator arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises the positive electrode sheet described in the first aspect or the positive electrode sheet prepared by the preparation method described in the second aspect.
[0026] The battery provided by the present application has high capacity, long cycle life, and excellent high temperature and low temperature performance.
[0027] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the battery described in the third aspect.
[0028] The electrical equipment provided in this application has excellent electrochemical performance, long service life and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0030] Figure 1 A schematic diagram of the cross-sectional structure of a positive electrode sheet provided in one embodiment of the present application;
[0031] Figure 2 A schematic diagram of the cross-sectional structure of a positive electrode plate provided in another embodiment of the present application. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] See also Figure 1, is a schematic diagram of the cross-sectional structure of a positive electrode plate provided in one embodiment of the present application, the positive electrode plate 100 includes a positive electrode current collector 10 and an active layer arranged on at least one side of the positive electrode current collector 10, the active layer includes a first active layer 11, a second active layer 12 and a third active layer 13 stacked in sequence from the side close to the positive electrode current collector 10 to the side away from the positive electrode current collector 10, the first active layer 11 includes a first active material, the second active layer 12 includes a second active material, and the third active layer 13 includes a third active material, the first active material, the second active material and the third active material are selected from three types of active materials: Prussian blue compounds, layered oxides or polyanion compounds, and the first active material, the second active material and the third active material are different types of active materials. The positive electrode sheet provided by the present application has an active layer with three types of stacked positive electrode active materials, namely, Prussian blue compound, layered oxide and polyanion compound. The Prussian blue compound has low environmental cost and can reduce the cost of active layer materials. The layered compound has a high voltage range and high specific capacity, which can improve the specific capacity of the positive electrode active layer and the energy density of the battery. The polyanion compound has good thermal stability and structural stability, which can improve the cycle performance of the battery. The three types of positive electrode active layer stacking can effectively alleviate the influence of sufficient contact between different materials on their respective performances. By combining the advantages of the three types of active materials, the specific capacity of the positive electrode active material can be further improved, and the energy density and cycle stability of the battery can be improved. The positive electrode sheet provided by the present application has the advantages of high specific capacity, good energy density and good cycle stability under the synergistic effect of three different types of positive electrode active materials, which is conducive to improving the electrochemical performance of the battery.
[0034] In the present application, the first active material, the second active material and the third active material are selected from three types of active materials, namely, Prussian blue compounds, layered oxides or polyanion compounds, and the first active material, the second active material and the third active material are different types of active materials. That is to say, the active materials in the first active layer, the second active layer and the third active layer are three different types of active materials. In some embodiments, the first active material is a layered oxide, in which case the second active material may be a Prussian blue compound and the third active material may be a polyanion compound; or the second active material may be a polyanion compound and the third active material may be a Prussian blue compound. In some embodiments, the first active material is a polyanion compound, in which case the second active material may be a layered oxide and the third active material may be a Prussian blue compound; or the second active material may be a Prussian blue compound and the third active material may be a layered oxide. In some embodiments, the first active material is a Prussian blue compound, in which case the second active material may be a layered oxide and the third active material may be a polyanion compound; or the second active material may be a polyanion compound and the third active material may be a layered oxide.
[0035] In one embodiment of the present application, the first active layer, the second active layer and the third active layer are disposed on only one side of the positive electrode current collector.
[0036] See also Figure 2 , is a schematic diagram of the cross-sectional structure of a positive electrode sheet provided in another embodiment of the present application, wherein the positive electrode sheet 100 includes a positive electrode current collector 10, and a first active layer 11, a second active layer 12, and a third active layer 13 are provided on both sides of the positive electrode current collector 10. The first active material in the first active layer on both sides of the positive electrode current collector may be the same or different, the second active material in the second active layer on both sides may be the same or different, and the third active material in the third active layer on both sides may be the same or different. In one embodiment of the present application, the first active layer on both sides of the positive electrode current collector is the same, the second active layer is the same, and the third active layer is the same.
[0037] In one embodiment of the present application, the second active material is a layered oxide. In addition to a high voltage range and a high specific capacity, the layered oxide also has a high tap density, which further improves the energy density; however, the structural stability of the layered oxide is poor. By placing the layered oxide in the middle, the first active layer and the third active layer are protected, the rolling stress is buffered, and the layered oxide particles are prevented from breaking during the rolling of the pole piece; in addition, the side reactions of high current density and electrolyte erosion, which cause the electrochemical performance to decrease, can be alleviated.
[0038] In one embodiment of the present application, the first active material is a Prussian blue compound, the second active material is a layered oxide, and the third active material is a polyanion compound. In the first active layer, the Prussian blue compound has a higher water absorption than the layered oxide and the polyanion compound, and is arranged on the side close to the positive electrode current collector, which can slow down the infiltration of external water after the positive electrode is baked; in the second active layer, the layered oxide has a higher tap density, which can further improve the energy density of the electrode, but the structural stability of the layered oxide is poor. By arranging the layered oxide in the middle, the protection of the first active layer and the third active layer buffers the rolling stress and prevents the layered oxide particles from breaking during the rolling of the electrode; in addition, it can also alleviate the side reactions of high current density and electrolyte erosion, resulting in reduced electrochemical performance; in the third active layer, the polyanion compound has high thermal stability and structural stability, and is arranged on the side close to the electrolyte, which can effectively alleviate the electrolyte erosion of the other two layers and improve the cycle life of the battery.
[0039] In the embodiment of the present application, the Prussian blue compound is easy to absorb water and is arranged near the positive electrode current collector, which is beneficial to reduce the side reactions of the battery during storage or circulation and improve the cycle stability of the positive electrode active material. Specifically, the Prussian blue compound can include but is not limited to Na2Zn3[Fe(CN)6]2·xH2O (x≤0.1), Na 1.72 MnFe(CN)6、Na 1.92 At least one of FeFe(CN)6 and Na2CoFe(CN)6. In one embodiment of the present application, the Prussian blue compound may be Na2Zn3[Fe(CN)6]2·xH2O. In another embodiment of the present application, the Prussian blue compound may be Na 1.72 MnFe(CN)6.
[0040] In the embodiment of the present application, the layered oxide has good stability and is conducive to improving the cycle stability of the positive electrode. Specifically, the layered oxide may include but is not limited to at least one of sodium nickelate, sodium ferrite, sodium chromate, copper iron manganese oxide and sodium ferrite-based oxide. In one embodiment of the present application, the layered oxide may be sodium nickelate. In another embodiment of the present application, the layered oxide may be copper iron manganese oxide.
[0041] In the embodiment of the present application, the polyanion compound has high thermal stability and structural stability, which is beneficial to improving the cycle stability of the battery. Specifically, the polyanion compound may include but is not limited to at least one of sodium iron sulfate, sodium iron phosphate, sodium vanadium phosphate and sodium vanadium fluorophosphate. In one embodiment of the present application, the polyanion compound may be sodium iron sulfate. In another embodiment of the present application, the polyanion compound may be sodium iron phosphate.
[0042] In one embodiment of the present application, in the active layer, the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is (1.5-2.5): (4-6): (2.5-3.5). An appropriate mass ratio can enhance their synergistic effect, further enhance the specific capacity of the positive electrode active layer, and enhance the energy density and cycle stability of the battery. Specifically, the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound can be, but is not limited to, 1.5:5:3.5, 1.5:6:2.5, 2:5:3, 2:5.5:2.5, 2.5:5:2.5 or 2.5:4:3.5, etc. In one embodiment of the present application, in the active layer, the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound can be (1.5-2): (4-5): (2.5-3). In another embodiment of the present application, in the active layer, the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound can be (25-3.5): (5-6): (3-3.5).
[0043] In one embodiment of the present application, in the first active layer, the mass percentage of the first active material is 90%-97%, and an appropriate amount of the first active material can increase the specific capacity of the positive electrode. Specifically, the mass percentage of the first active material can be, but is not limited to, 90%, 91%, 92%, 93%, 94%, 95%, 96% or 97%, etc. In one embodiment of the present application, in the first active layer, the mass percentage of the first active material can be 90%-94%. In another embodiment of the present application, in the first active layer, the mass percentage of the first active material can be 93%-97%.
[0044] In one embodiment of the present application, in the second active layer, the mass percentage of the second active material is 90%-97%, and an appropriate amount of the second active material can increase the specific capacity of the positive electrode. Specifically, the mass percentage of the second active material can be, but is not limited to, 90%, 91%, 92%, 93%, 94%, 95%, 96% or 97%, etc. In one embodiment of the present application, in the second active layer, the mass percentage of the second active material can be 90%-94%. In another embodiment of the present application, in the second active layer, the mass percentage of the second active material can be 93%-95%.
[0045] In one embodiment of the present application, in the third active layer, the mass percentage of the third active material is 90%-97%, and an appropriate amount of the third active material can increase the specific capacity of the positive electrode sheet. Specifically, the mass percentage of the third active material can be, but is not limited to, 90%, 91%, 92%, 93%, 94%, 95%, 96% or 97%, etc. In one embodiment of the present application, in the third active layer, the mass percentage of the third active material can be 90%-94%. In another embodiment of the present application, in the third active layer, the mass percentage of the third active material can be 93%-95%. In one embodiment of the present application, the first active layer, the second active layer and the third active layer also include a conductive agent and a binder, which can improve the conductivity and structural stability of the first active layer, the second active layer and the third active layer.
[0046] In one embodiment of the present application, the conductive agent can improve the conductivity of the active layer. Specifically, the conductive agent may include but is not limited to at least one of carbon nanotubes, acetylene black, graphene, graphite and conductive carbon black; the binder may include but is not limited to at least one of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the conductive agent may be carbon nanotubes and conductive carbon black, and the binder may be polyvinylidene fluoride. In some embodiments, the conductive agents in the first active layer, the second active layer and the third active layer may be the same or different; the binders in the first active layer, the second active layer and the third active layer may be the same or different.
[0047] In one embodiment of the present application, the first active layer, the second active layer and the third active layer further include a dispersant. Specifically, the dispersant may include but is not limited to at least one of polyvinyl pyrrolidone, N-methyl pyrrolidone, dimethyl carbonate and ethylene carbonate. In one embodiment of the present application, the dispersant may be polyvinyl pyrrolidone. In some embodiments, the dispersants in the first active layer, the second active layer and the third active layer may be the same or different.
[0048] In one embodiment of the present application, in the active layer, the mass percentage of the conductive agent is 1.5%-3%, and an appropriate amount of the conductive agent can improve the conductivity of the active layer. Specifically, in the active layer, the mass percentage of the conductive agent can be, but is not limited to, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%, etc. In one embodiment of the present application, in the active layer, the mass percentage of the conductive agent can be 1.5%-1.8%. In another embodiment of the present application, in the active layer, the mass percentage of the conductive agent can be 1.7%-2%.
[0049] In one embodiment of the present application, in the active layer, the mass percentage of the binder is 2%-2.5%, and an appropriate amount of binder can improve the structural stability of the positive electrode sheet. Specifically, in the active layer, the mass percentage of the binder can be, but is not limited to, 2%, 2.1%, 2.2%, 2.3%, 2.4% or 2.5%, etc. In one embodiment of the present application, in the active layer, the mass percentage of the binder can be 2%-2.3%. In another embodiment of the present application, in the active layer, the mass percentage of the binder can be 2.3%-2.5%.
[0050] In one embodiment of the present application, in the first active layer, the mass ratio of the first active material, the conductive agent and the binder is (94.5-96.5): (1.5-3): (2-2.5), and the appropriate mass ratio can improve the conductivity and specific capacity of the first active layer. Specifically, in the first active layer, the mass ratio of the first active material, the conductive agent and the binder can be, but is not limited to, 94.5:3:2.5, 95:2.5:2.5, 95.5:2.5:2, 95.5:2:2.5, 96:2:2 or 96.5:1.5:2, etc. In one embodiment of the present application, in the first active layer, the mass ratio of the first active material, the conductive agent and the binder can be (94.5-95.5): (1.5-2): (2-2.4). In another embodiment of the present application, in the first active layer, the mass ratio of the first active material, the conductive agent and the binder may be (95.5-96.5):(2-3.0):(2.3-2.5).
[0051] In one embodiment of the present application, in the second active layer, the mass ratio of the second active material, the conductive agent and the binder is (94.5-96.5): (1.5-3): (2-2.5), and the appropriate mass ratio can improve the conductivity and specific capacity of the second active layer. Specifically, in the second active layer, the mass ratio of the second active material, the conductive agent and the binder can be, but is not limited to, 94.5:3:2.5, 95:2.5:2.5, 95.5:2.5:2, 95.5:2:2.5, 96:2:2 or 96.5:1.5:2, etc. In one embodiment of the present application, in the second active layer, the mass ratio of the second active material, the conductive agent and the binder can be (94.5-95.5): (1.5-2): (2-2.4). In another embodiment of the present application, in the second active layer, the mass ratio of the second active material, the conductive agent and the binder may be (95.5-96.5):(2-3.0):(2.3-2.5).
[0052] In one embodiment of the present application, in the third active layer, the mass ratio of the third active material, the conductive agent and the binder is (94.5-96.5): (1.5-3): (2-2.5), and the appropriate mass ratio can improve the conductivity and specific capacity of the third active layer. Specifically, in the third active layer, the mass ratio of the third active material, the conductive agent and the binder can be, but is not limited to, 94.5:3:2.5, 95:2.5:2.5, 95.5:2.5:2, 95.5:2:2.5, 96:2:2 or 96.5:1.5:2, etc. In one embodiment of the present application, in the third active layer, the mass ratio of the third active material, the conductive agent and the binder can be (94.5-95.5): (1.5-2): (2-2.4). In another embodiment of the present application, in the third active layer, the mass ratio of the third active material, the conductive agent and the binder may be (95.5-96.5):(2-3.0):(2.3-2.5).
[0053] In one embodiment of the present application, the third active material is a polyanion compound, the mass content of the conductive agent in the third active layer is greater than the mass content of the conductive agent in the first active layer, and / or the mass content of the conductive agent in the third active layer is greater than the mass content of the conductive agent in the second active layer. The conductivity of the polyanion is poor, and increasing the content of the conductive agent increases the conductivity of the third active layer, thereby improving the electrochemical performance of the battery.
[0054] The present application also provides a method for preparing a positive electrode sheet, comprising:
[0055] The surfaces of both sides of the positive electrode current collector are coated with the first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry in sequence, and the positive electrode sheet is obtained after drying; the first positive electrode slurry includes a first active material, the second positive electrode slurry includes a second active material, the third positive electrode slurry includes a third active material, the first active material, the second active material and the third active material are selected from three types of active materials: Prussian blue compound, layered oxide or polyanion compound, and the first active material, the second active material and the third active material are different types of active materials. The preparation method provided in the present application is novel, the preparation process is simple, the preparation cost is low, the prepared positive electrode sheet has high specific capacity, good energy density and good cycle stability, which is conducive to the industrial production of the positive electrode sheet.
[0056] In one embodiment of the present application, the first positive electrode slurry is used to form a first active layer, the second positive electrode slurry is used to form a second active layer, and the third positive electrode slurry is used to form a third active layer. The selection of active materials in each slurry refers to the description of the aforementioned active layer and will not be repeated here.
[0057] In one embodiment of the present application, the first positive electrode slurry also includes a conductive agent and a binder, which can improve the coating ability of the first positive electrode slurry and is beneficial to improving the electrochemical performance and structural stability of the positive electrode sheet.
[0058] In one embodiment of the present application, the mass ratio of the first active material, the conductive agent and the binder is (90-97): (1.5-3): (2-2.5), which can improve the cycle stability, specific capacity and energy density of the first active layer. Specifically, the mass ratio of the first active material, the conductive agent and the binder can be, but is not limited to, 94.5:3:2.5, 95:2.5:2.5, 95.5:2.5:2, 95.5:2:2.5, 96:2:2 or 96.5:1.5:2, etc. In one embodiment of the present application, the mass ratio of the active material, the conductive agent and the binder can be (90-94): (1.5-1.8): (2-2.4). In another embodiment of the present application, the mass ratio of the first active material, the conductive agent and the binder can be (93-96): (1.7-2): (2.3-2.5).
[0059] In one embodiment of the present application, the first positive electrode slurry also includes a dispersant, and the mass ratio of the first active material, the conductive agent, the binder and the dispersant is (90-96): (1.5-2): (2-2.5): (0-0.5), which can improve the cycle stability, specific capacity and energy density of the first active layer. Specifically, the mass ratio of the first active material, the conductive agent, the binder and the dispersant can be, but is not limited to, 90:1.5:2:0, 91:1.5:2.1:0.1, 92:1.6:2.2:0.2, 93:1.8:2.3:0.3, 94:1.8:2.4:0.4 or 96:2:2.5:0.5, etc. In one embodiment of the present application, the mass ratio of the first active material, the conductive agent, the binder and the dispersant can be (90-94): (1.5-1.8): (2-2.4). In another embodiment of the present application, the mass ratio of the first active material, the conductive agent, the binder and the dispersant may be (93-96): (1.7-2): (2.3-2.5): (0.2-0.5).
[0060] In one embodiment of the present application, the second positive electrode slurry also includes a conductive agent and a binder, which can improve the coating ability of the second positive electrode slurry and is beneficial to improving the electrochemical performance and structural stability of the positive electrode sheet.
[0061] In one embodiment of the present application, the mass ratio of the second active material, the conductive agent and the binder is (90-96): (1.5-2): (2-2.5), which can improve the cycle stability, specific capacity and energy density of the second active layer. Specifically, the mass ratio of the second active material, the conductive agent and the binder can be, but is not limited to, 94.5:3:2.5, 95:2.5:2.5, 95.5:2.5:2, 95.5:2:2.5, 96:2:2 or 96.5:1.5:2, etc. In one embodiment of the present application, the mass ratio of the second active material, the conductive agent and the binder can be (90-94): (1.5-1.8): (2-2.4). In another embodiment of the present application, the mass ratio of the second active material, the conductive agent and the binder can be (93-96): (1.7-2): (2.3-2.5).
[0062] In one embodiment of the present application, the second positive electrode slurry further includes a dispersant, and the mass ratio of the second active material, the conductive agent, the binder and the dispersant is (90-96): (1.5-2): (2-2.5): (0-0.5), which can improve the cycle stability, specific capacity and energy density of the second active layer. Specifically, the mass ratio of the second active material, the conductive agent, the binder and the dispersant can be, but is not limited to, 90:1.5:2:0, 91:1.5:2.1:0.1, 92:1.6:2.2:0.2, 93:1.8:2.3:0.3, 94:1.8:2.4:0.4 or 96:2:2.5:0.5, etc. In one embodiment of the present application, the mass ratio of the second active material, the conductive agent, the binder and the dispersant can be (90-94): (1.5-1.8): (2-2.4): (0-0.4). In another embodiment of the present application, the mass ratio of the second active material, the conductive agent, the binder and the dispersant may be (93-96): (1.7-2): (2.3-2.5): (0.2-0.5).
[0063] In one embodiment of the present application, the third positive electrode slurry also includes a conductive agent and a binder, which can improve the coating ability of the third positive electrode slurry and is beneficial to improving the electrochemical performance and structural stability of the positive electrode sheet.
[0064] In one embodiment of the present application, the mass ratio of the third active material, the conductive agent and the binder is (90-96): (1.5-2): (2-2.5), which can improve the cycle stability, specific capacity and energy density of the third active layer. Specifically, the mass ratio of the third active material, the conductive agent and the binder can be, but is not limited to, 94.5:3:2.5, 95:2.5:2.5, 95.5:2.5:2, 95.5:2:2.5, 96:2:2 or 96.5:1.5:2, etc. In one embodiment of the present application, the mass ratio of the third active material, the conductive agent and the binder can be (90-94): (1.5-1.8): (2-2.4). In another embodiment of the present application, the mass ratio of the third active material, the conductive agent and the binder can be (93-96): (1.7-2): (2.3-2.5).
[0065] In one embodiment of the present application, the third positive electrode slurry further includes a dispersant, and the mass ratio of the third active material, the conductive agent, the binder and the dispersant is (90-96): (1.5-2): (2-2.5): (0-0.5), which can improve the cycle stability, specific capacity and energy density of the third active layer. Specifically, the mass ratio of the third active material, the conductive agent, the binder and the dispersant can be, but is not limited to, 90:1.5:2:0, 91:1.5:2.1:0.1, 92:1.6:2.2:0.2, 93:1.8:2.3:0.3, 94:1.8:2.4:0.4 or 96:2:2.5:0.5, etc. In one embodiment of the present application, the mass ratio of the third active material, the conductive agent, the binder and the dispersant can be (90-94): (1.5-1.8): (2-2.4): (0-0.4). In another embodiment of the present application, the mass ratio of the third active material, the conductive agent, the binder and the dispersant may be (93-96): (1.7-2): (2.3-2.5): (0.2-0.5).
[0066] In one embodiment of the present application, the solid content of the first positive electrode slurry, the second positive electrode slurry, and the third positive electrode slurry is 50%-55%, which is conducive to improving the coating ability of the positive electrode slurry and improving the coating uniformity. Specifically, the solid content of the positive electrode slurry can be, but is not limited to, 50%, 51%, 52%, 53%, 54% or 55%, etc.
[0067] In one embodiment of the present application, the viscosity of the first positive electrode slurry, the second positive electrode slurry, and the third positive electrode slurry is 1500Pa·s-8000Pa·s. The appropriate viscosity can improve the conductivity of the positive electrode slurry and improve the bonding ability of the positive electrode sheet. Specifically, the viscosity of the positive electrode slurry can be, but is not limited to, 1500Pa·s, 2500Pa·s, 3000Pa·s, 4000Pa·s, 5000Pa·s, 6000Pa·s, 7000Pa·s or 8000Pa·s, etc.
[0068] The present application also provides a battery, comprising a negative electrode sheet and a positive electrode sheet provided by any one of the above embodiments. The positive electrode sheet has high energy density, high cycle performance, and excellent specific capacity, which increases the battery capacity of the battery, improves the cycle performance of the battery, and prolongs the service life of the battery, which is conducive to the wide application of the battery.
[0069] In one embodiment of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector. Specifically, the negative electrode current collector may include, but is not limited to, at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the negative electrode current collector may be copper foil. In one embodiment of the present application, the negative electrode active layer includes a negative electrode active material, and the negative electrode active material may include, but is not limited to, at least one of silicon, tin, germanium, lithium and alloys thereof and carbon materials. Among them, the carbon material may include, but is not limited to, at least one of non-graphitized carbon, graphite, pyrolytic carbon, coke and activated carbon. In one embodiment of the present application, the negative electrode active material may be a carbon material. In another embodiment of the present application, the negative electrode active material may be a silicon material.
[0070] In one embodiment of the present application, the negative electrode active layer also includes a negative electrode conductive agent. The negative electrode conductive agent can increase the conductivity between active materials and improve electronic conductivity. Specifically, the negative electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the negative electrode conductive agent may be graphite. In another embodiment of the present application, the negative electrode conductive agent may be carbon black.
[0071] In one embodiment of the present application, the negative electrode active layer further includes a negative electrode binder, which can improve the binding ability of the components in the negative electrode active layer and improve the binding ability between the negative electrode active layer and the negative electrode current collector. Specifically, the negative electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the negative electrode binder can be polyvinylidene fluoride.
[0072] In one embodiment of the present application, the battery further comprises an electrolyte. At least part of the positive electrode sheet and at least part of the negative electrode sheet are immersed in the electrolyte. The electrolyte of the present application is not particularly limited, and can be, but not limited to, a substance that can be used as a battery electrolyte in the art. In one embodiment of the present application, the electrolyte can be sodium hexafluorophosphate salt.
[0073] The present application also provides an electrical device, which includes the battery described in any of the above embodiments. The electrical device provided in the present application has high energy density, good cycle performance, high safety performance, excellent comprehensive electrochemical performance, and strong market competitiveness. Electrical equipment includes mobile phones, tablets, watches, VR glasses, vehicles, etc. In one embodiment of the present application, the battery can be used in vehicles to improve the safety of vehicle electricity use and increase the service life of car batteries. In another embodiment of the present application, the battery can also be used in mobile phones, which can increase the battery capacity of mobile phones, improve the battery life and safety of use.
[0074] The effect of the technical solution of the present application is further illustrated below through specific examples.
[0075] Example 1
[0076] The first positive electrode slurry is coated on both sides of the positive electrode current collector (aluminum foil), and the first active layer is obtained after drying. The second positive electrode slurry is coated on the surface of the first active layer, and the second active layer is obtained after drying. The third positive electrode slurry is coated on the surface of the second active layer, and the positive electrode sheet is obtained after drying, wherein:
[0077] The first positive electrode slurry includes, by mass percentage, 95.4% of the first active material (Prussian blue compound (Na2Zn3[Fe(CN)6]2·xH2O)), 1.8% of the conductive agent (carbon nanotubes and conductive carbon black), 2.5% of the binder (polyvinylidene fluoride) and 0.3% of the dispersant (polyvinyl pyrrolidone), and the viscosity of the first positive electrode slurry is 2560 Pa·s;
[0078] The second positive electrode slurry includes 95.4% of the second active material (layered oxide (O3-NaFe 0.33 Ni 0.33 Mn 0.33 O2), 1.8% of conductive agent (carbon nanotubes and conductive carbon black), 2.5% of binder (polyvinylidene fluoride) and 0.3% of dispersant (polyvinyl pyrrolidone), the viscosity of the second positive electrode slurry is 2200Pa·s;
[0079] The third positive electrode slurry includes 95% of the third active material (polyanion compound (Na7V4(P2O7)4(PO4))), 2.2% of the conductive agent (carbon nanotubes and conductive carbon black), 2.5% of the binder (polyvinylidene fluoride) and 0.3% of the dispersant (polyvinyl pyrrolidone) by mass percentage, and the viscosity of the third positive electrode slurry is 2600 Pa·s;
[0080] By controlling the coating amounts of the first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry, the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound in the entire active layer is 2:5.5:2.5.
[0081] Example 2
[0082] The difference from Example 1 is that the first active material is a polyanion compound, the third active material is a Prussian blue compound, and the material components and mass ratios in each layer remain unchanged.
[0083] Example 3
[0084] The difference from Example 1 is that the first active material is a polyanion compound, the second active material is a Prussian blue compound, the third active material is a layered oxide, and the material components and mass ratios in each layer remain unchanged.
[0085] Example 4
[0086] The difference from Example 1 is that the second active material is a polyanion compound, the third active material is a layered oxide, and the material components and mass ratio in each layer remain unchanged.
[0087] Example 5
[0088] The difference from Example 1 is that, by mass percentage, the third positive electrode slurry includes 95.4% of the third active material (polyanion compound (Na7V4(P2O7)4(PO4))), 1.8% of the third conductive agent (carbon nanotubes and conductive carbon black), 2.5% of the third binder (polyvinylidene fluoride) and 0.3% of the third dispersant (polyvinyl pyrrolidone), and the material components and mass ratios in other layers remain unchanged.
[0089] Example 6
[0090] The difference from Example 1 is that the coating amounts of the first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry are controlled so that the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is 1.5:6:3.5.
[0091] Example 7
[0092] The difference from Example 1 is that the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is 2.5:4:3.5 by controlling the coating amounts of the first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry.
[0093] Example 8
[0094] The difference from Example 1 is that the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is 1.5:5:3.5 by controlling the coating amounts of the first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry.
[0095] Example 9
[0096] The difference from Example 1 is that the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is 1.5:4:4.5 by controlling the coating amounts of the first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry.
[0097] Example 10
[0098] The difference from Example 1 is that the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is 1:4:5 by controlling the coating amounts of the first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry.
[0099] Comparative Example 1
[0100] The difference from Example 1 is that, by mass percentage, the positive electrode slurry includes 95.4% of positive electrode active material (19.08% of Prussian blue compound (Na2Zn3[Fe(CN)6]2·xH2O), 52.47% of layered oxide (O3-NaFe 0.33 Ni 0.33 Mn 0.33 O2) and 23.85% of polyanionic compound (Na7V4(P2O7)4(PO4))), 1.8% of positive electrode conductive agent (carbon nanotubes and conductive carbon black), 2.5% of positive electrode binder (polyvinylidene fluoride) and 0.3% of positive electrode dispersant (polyvinyl pyrrolidone), the slurry viscosity is 2360Pa·s;
[0101] The positive electrode slurry is coated on both sides of the positive electrode current collector and dried to obtain the positive electrode sheet.
[0102] Comparative Example 2
[0103] The difference from Example 1 is that the first positive electrode slurry is coated on both sides of the positive electrode current collector, and the positive electrode sheet is obtained after drying, and the components and mass ratio of the first positive electrode slurry remain unchanged.
[0104] Comparative Example 3
[0105] The difference from Example 1 is that the second positive electrode slurry is coated on both sides of the positive electrode current collector, and the positive electrode sheet is obtained after drying, and the components and mass ratio of the second positive electrode slurry remain unchanged.
[0106] Comparative Example 4
[0107] The difference from Example 1 is that the third positive electrode slurry is coated on both sides of the positive electrode current collector, and the positive electrode sheet is obtained after drying, and the components and mass ratio of the third positive electrode slurry remain unchanged.
[0108] Comparative Example 5
[0109] The difference from Example 1 is that the first positive electrode slurry is coated on both sides of the positive electrode current collector, and the first active layer is obtained after drying, and the second positive electrode slurry is coated on the surface of the first active layer, and the positive electrode sheet is obtained after drying, and the components and mass ratios in the positive electrode slurry remain unchanged.
[0110] Comparative Example 6
[0111] The difference from Example 1 is that the first positive electrode slurry is coated on both sides of the positive electrode current collector, and the first active layer is obtained after drying, and the third positive electrode slurry is coated on the surface of the first active layer, and the positive electrode sheet is obtained after drying, and the components and mass ratios in the positive electrode slurry remain unchanged.
[0112] Comparative Example 7
[0113] The difference from Example 1 is that the second positive electrode slurry is coated on both sides of the positive electrode current collector, and the second active layer is obtained after drying, and the third positive electrode slurry is coated on the surface of the second active layer, and the positive electrode sheet is obtained after drying, and the components and mass ratios in the positive electrode slurry remain unchanged.
[0114] Performance Testing
[0115] The above-mentioned Examples 1-10 and Comparative Examples 1-7 were wound with negative electrode sheets and injected with liquid (the electrolyte in the electrolyte was 1.0 M sodium hexafluorophosphate, and the solvent was a mixture of EC, EMC, DMC and DEC) to obtain a soft-pack battery with a capacity of 20 Ah, wherein the negative electrode sheet was obtained by coating the negative electrode slurry on two layers of the negative electrode collector and drying; in terms of mass percentage, the negative electrode slurry included 95.8% of negative electrode active material (hard carbon), 1.5% of conductive agent (conductive carbon black), 1.5% of binder (styrene-butadiene rubber) and 1.2% of dispersant (carboxymethyl cellulose).
[0116] The batteries prepared in the above-mentioned embodiments 1-10 and comparative examples 1-7 were tested for specific capacity and energy density according to the disassembly test method of the whole vehicle use condition. The test method is as follows: in the voltage range of 2.5V-3.8V, 1C&1C was used for charge and discharge test, and 3 cycles were performed. The discharge capacity and energy of the third cycle were taken to calculate the specific capacity of the active material and the energy density of the battery, wherein specific capacity = battery discharge capacity ÷ active material mass; battery energy density = discharge energy ÷ battery mass; the results are shown in Table 1.
[0117] The batteries prepared in the above-mentioned embodiments 1-10 and comparative examples 1-7 were tested for their low-temperature discharge performance according to the whole vehicle use disassembly test method. The test method is as follows: at -30°C and 50% SOC, discharge at 5C for 2s and record the voltage at the end of discharge. The results are shown in Table 1.
[0118] The batteries prepared in the above-mentioned embodiments 1-10 and comparative examples 1-7 were tested for their cycle performance. The test method was as follows: at 60°C, in the voltage range of 2.5-3.8V, a charge and discharge test was performed using 1C&1C. The test was stopped when the capacity retention rate was lower than 80%, and the number of cycles was recorded. The results are shown in Table 1.
[0119] Table 1 Performance test results
[0120]
[0121]
[0122] It can be seen from Examples 1-10 and Comparative Examples 1-7 that the positive electrode sheet provided by the present application has three types of stacked positive active materials, namely, Prussian blue compounds, layered oxides and polyanion compounds. Under synergistic effects, the specific capacity of the positive active material layer can be increased, the energy density and cycle performance of the battery can be increased, and the battery has excellent low temperature performance. It can be seen from Examples 1 and 2-4 that when the first active material is a Prussian blue compound, the second active material is a layered oxide, and the third active material is a polyanion compound, it is beneficial to further increase the specific capacity of the positive electrode sheet, increase the energy density and cycle number of the battery, and make the battery have excellent low temperature performance. It can be seen from Examples 1 and 5 that when the active material is a polyanion compound, the appropriate content of the conductive agent can increase the conductivity of the active material and improve the low temperature discharge performance of the battery. It can be seen from Examples 1 and 6-10 that the mass ratio of suitable Prussian blue compounds, layered oxides and polyanion compounds can further improve the electrochemical performance of the battery. It can be seen from Example 1 and Comparative Examples 1-7 that when the positive electrode plate has three types of stacked positive electrode active materials, namely, Prussian blue compound, layered oxide and polyanion compound, their synergistic effect can improve the energy density and cycle performance of the battery.
[0123] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode plate includes a positive electrode current collector and an active layer arranged on at least one side of the positive electrode current collector, the active layer includes a first active layer, a second active layer and a third active layer stacked in sequence from a side close to the positive electrode current collector to a side away from the positive electrode current collector, the first active layer includes a first active material, the second active layer includes a second active material, the third active layer includes a third active material, the first active material, the second active material and the third active material are selected from three types of active materials: Prussian blue compounds, layered oxides or polyanion compounds, and the first active material, the second active material and the third active material are different types of active materials.
2. The positive electrode sheet according to claim 1, characterized in that: The second active material is a layered oxide.
3. The positive electrode sheet according to claim 1, characterized in that: The first active material is a Prussian blue compound, the second active material is a layered oxide, and the third active material is a polyanion compound.
4. The positive electrode sheet according to claim 1, characterized in that: In the active layer, the mass ratio of the Prussian blue compound, the layered oxide and the polyanion compound is (1.5-2.5):(4-6):(2.5-3.5).
5. The positive electrode sheet according to claim 1, characterized in that: In the first active layer, the mass percentage of the first active material is 90%-97%; In the second active layer, the mass percentage of the second active material is 90%-97%; In the third active layer, the mass percentage of the third active material is 90%-97%.
6. The positive electrode sheet according to claim 1, characterized in that: The Prussian blue compound includes Na2Zn3[Fe(CN)6]2·xH2O (x≤0.1), Na 1.72 MnFe(CN)6、Na 1.92 At least one of FeFe(CN)6 and Na2CoFe(CN)6; The layered oxide includes at least one of sodium nickelate, sodium ferrite, sodium chromate, copper iron manganese oxide and sodium ferrite-based oxide; The polyanion compound includes at least one of sodium ferric sulfate, sodium ferric phosphate, sodium vanadium phosphate and sodium vanadium fluorophosphate.
7. The positive electrode sheet according to claim 1, characterized in that: The first active layer further includes a conductive agent and a binder; the second active layer further includes a conductive agent and a binder; and the third active layer further includes a conductive agent and a binder.
8. The positive electrode sheet according to claim 7, characterized in that: The third active material is a polyanion compound, and the mass content of the conductive agent in the third active layer is greater than the mass content of the conductive agent in the first active layer; And / or the mass content of the conductive agent in the third active layer is greater than the mass content of the conductive agent in the second active layer.
9. The positive electrode sheet according to any one of claims 7 to 8, characterized in that: In the first active layer, the mass ratio of the first active material, the conductive agent and the binder is (94.5-96.5):(1.5-3):(2-2.5); In the second active layer, the mass ratio of the second active material, the conductive agent and the binder is (94.5-96.5):(1.5-3):(2-2.5); In the third active layer, the mass ratio of the third active material, the conductive agent and the binder is (94.5-96.5):(1.5-3):(2-2.5).
10. A method for preparing a positive electrode sheet according to any one of claims 1 to 9, characterized in that: include: The first positive electrode slurry, the second positive electrode slurry and the third positive electrode slurry are sequentially coated on at least one side of the surface of the positive electrode collector, and a positive electrode sheet is obtained after drying; the first positive electrode slurry includes a first active material, the second positive electrode slurry includes a second active material, the third positive electrode slurry includes a third active material, the third active layer includes a third active material, the first active material, the second active material and the third active material are selected from three types of active materials: Prussian blue compounds, layered oxides or polyanion compounds, and the first active material, the second active material and the third active material are different types of active materials.
11. The preparation method according to claim 10, characterized in that: The first positive electrode slurry further includes a conductive agent and a binder, and the mass ratio of the first active material, the conductive agent and the binder in the first positive electrode slurry is (94.5-96.5):(1.5-3):(2-2.5); The second positive electrode slurry further includes a conductive agent and a binder, and the mass ratio of the second active material, the conductive agent and the binder in the second positive electrode slurry is (94.5-96.5):(1.5-3):(2-2.5); The third positive electrode slurry further includes a conductive agent and a binder. The mass ratio of the third active material, the conductive agent and the binder in the third positive electrode slurry is (94.5-96.5):(1.5-3):(2-2.5).
12. The preparation method according to claim 10, characterized in that: The viscosity of the first positive electrode slurry is 1500 Pa·s-8000 Pa·s; the viscosity of the second positive electrode slurry is 1500 Pa·s-8000 Pa·s; and the viscosity of the third positive electrode slurry is 1500 Pa·s-8000 Pa·s.
13. A battery, characterized in that: The battery comprises a positive electrode sheet and a negative electrode sheet, and a separator arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises the positive electrode sheet according to any one of claims 1 to 9 or the positive electrode sheet prepared by the preparation method according to any one of claims 10 to 12.
14. An electrical device, characterized in that: The electrical device comprises the battery according to claim 13.